Simulating maize/bean polycultures using functional-structural plant modelling - Rutjens, R. J. L. (2024)
Climate change, a growing global population and soil degradation put significant stress on food production and threaten food security, both on a global scale and in individual agricultural communities. This necessitates studies that explore sustainable agricultural intensification. Traditional farming systems have received increased attention, as aspects of these systems (such as niche complementarity) might provide sustainable solutions. This work centers around the three sisters, a polyculture of maize (Zea mays), bean (Phaseolus vulgaris) and squash (Cucurbita spp.), and the milpa, a complex Maya polyculture centered around maize and bean. Building on an existing functional-structural plant (FSP) model for maize, a novel FSP model for common bean is developed (in the XL language, on the GroIMP platform), encompassing twining behaviour and physical plant-plant interactions. This allows us to simulate maize/bean polycultures, where common bean climbs upwards around the maize stalk. As the model contains many input parameters, of which some are difficult or costly to parameterise, a global sensitivity analysis (GSA) is paramount for identifying (un)important parameters in the model. This decreases dimensionality of the large model parameter space. Efforts can then be concentrated on accurately estimating the most important input parameters. GSA is therefore performed on monocultures of maize and common bean (growing on poles). To this end, the popular Elementary Effects GSA method is adapted to make it suitable for models with dimensional inputs, inputs taking values on arbitrary intervals or discrete inputs. Our results show the benefit of performing GSA on plant models: for both maize and bean, less than 30% of input parameters where classified as important for most model outputs. In addition, performing GSA on plant models leads to new insights about both the model and the plant developmental processes it describes. The hope is that this work will inspire more plant modellers to routinely incorporate sensitivity analysis in their research. Subsequently, the model for maize and bean is used to assess architectural facilitation in light capture in maize/bean polycultures. Simulation results agree with experimental observations in the literature of overyielding in polycultures including maize and climbing bean. This indicates that aboveground processes (also) play an important role in the phenomenon of overperforming. In addition, it confirms that such agricultural systems may play a role in sustainable agricultural intensification. The maize/bean model presented in this work is one of the first examples of an aboveground FSP model of a polyculture with complex physical plant-plant interaction. Our results suggest that FSP modelling could be a valuable tool to investigate such agricultural systems. In this work, we have shown that it is possible to model maize/bean crop mixtures, making an aboveground model of the three sisters only a small step away.